Pharmacology, Efficacy and Safety of a Triple-Secured Fibrinogen Concentrate in Children Less than or Equal to 12 Years with Afibrinogenaemia - Djambas Khayat, Claudia; El Khorassani, Mohamed; Aytaç, Selin; Harroche, Annie; Dahmane, Amel; Pujol, Sonia; Henriet, Céline; de Moerloose, Philippe; Bridey, Françoise (Thrombosis and Haemostasis, 2020)
Objective To date, the use of a fibrinogen concentrate (FC) administered in children with inherited fibrinogen deficiency is poorly documented. Treatment modalities may differ from those of adults. The aim of this study was to investigate the pharmacokinetics (PK), efficacy (bleeding/surgery) and safety of a triple-secured FC (FibCLOT, LFB, France) in young patients aged of 12 years or less.Methods This was a prospective, non-comparative, multicentre, phase 2–3 study. Estimated PK parameters were based on population PK modelling. Target fibrinogen levels were 1.2 and 1.0 g/L for major and minor events, respectively. In vivo recovery (IVR) was calculated at study entry to tailor the dose.Results Sixteen afibrinogenaemia patients were treated with FC: 12 included in the PK study (6 aged ≤ 6 years and 6 aged 7–12 years). IVR at 1 hour post-infusion (geometric mean [coefficient of variation]) was 1.91 [20%] mg/dL per mg/kg and results were similar between the two age groups (1.87 [14%]) and (1.96 [27%]) with no statistical differences. Estimated half-life (t1/2) was 49.0 hours [12%] with no observed differences between groups (46.6 hours [10%] and 51.6 hours [12%]). Overall efficacy was rated as excellent/good in 96.9% of 32 bleeds and in 100% of 11 surgeries. Most of the events (39/43, 90.7%) were managed with one infusion. There was no serious adverse drug reaction.Conclusion Individually tailored dosing was efficacious in children who exhibited a lower IVR and shorter t1/2 than those previously reported in adolescent and adult patients emphasising the importance of individualised dose optimisation.
Keywords: afibrinogenaemia; clinical study; fibrinogen; children